Effectiveness of Fintech-Based Sharia Cooperative Development in the New Normal Era : Interpretative Structural Model Approach - Elida Elfi Barus; M.Yasir Nasution; Andri Soemitra (Publisher Cv. Inara, 2021)
In the Covid Pandemic 19, sharia cooperatives must be a solution for the welfare of their members and the UMKM that they support so that they can move up in class, but how if it is difficult to access, therefore sharia cooperatives must be digital-based and include collaborating with fintech. This study tries to answer the problems that occur, strategies, and stakeholders involved in the development of Islamic cooperatives in collaboration with sharia fintech in Indonesia using the Interpretive Structural Model (ISM) approach. The core problem faced in developing sharia cooperatives in collaboration with sharia fintech is the lack of education and promotion of Islamic financial institutions collaboration, especially in sharia cooperatives with sharia fintech (E9), which initially became competitors to financial institutions because they were very flexible and fast and have become OJK's instructions that fintech must collaborate with financial institutions including sharia ones. Furthermore, it can be suggested for legislators, actors and drafter to constantly monitor and improve the process in the context of the progress and welfare of cooperatives and SMEs in Indonesia.